Using Participatory Methods to Explore Freedom of Religion and Belief Whose Reality Counts? - Howard, Jo; Tadros, Mariz (Bristol University Press, 2023)
EPDF and EPUB available Open Access under CC-BY-NC-ND licence. Examining countries where religious pluralism is in decline, including Iraq, India, Pakistan and Nigeria, this book brings together reflections, knowledge and learning about the daily experiences of religiously marginalized groups, generated using participatory research methods. It also showcases the participatory methodologies implemented by its international team of contributors and highlights the importance of using non-extractive methods for engaging with participants.